Biodegradability and Safety Study of LifeMesh™, a Novel Self-adhesive Mesh, in Sprague-Dawley Rats. (June 2019) - Ramot, Yuval; Kronfeld, Noam; Steiner, Michal; Klaiman, Guy; Hadid, Amir; Sudak, Michal; Nyska, Abraham
Self-adhesive meshes are being developed to avoid complications due to traumatic fixation methods. LifeMesh™ is a novel self-adhesive mesh with a biodegradable gelatin adhesive layer developed for hernia repair. The aim of this study was to assess the safety and biodegradability of LifeMesh in Sprague-Dawley (SD) rats for 6 weeks, in comparison to a bare polypropylene (BPP) mesh fixed with sutures. LifeMesh was tolerated well and its implantation did not result in any adverse local reaction, and its adhesive layer was substantially degraded after 4 weeks. Histopathological examination revealed that the presence of the adhesive contributed to a uniform thickness of the granulation tissue surrounding the mesh, in contrast to a nonuniform granulation tissue with BPP. Nonuniform granulation tissue suggests that there will be poorer integration of the mesh to the abdominal wall. The use of LifeMesh also resulted in less adhesions of internal organs with a smaller surface area of involvement. These findings lend support to the potential benefit of LifeMesh for hernia repair in humans and expand the available information on the typical histopathological findings expected with biodegradable implants in the peritoneal cavity of SD rats.